Efficient Fiscal Spending by Supranational Unions - Jenny Simon; Justin M. Valasek (Oesterreichische Nationalbank (OeNB), 2013)
We study fiscal spending by supranational unions, where participation is voluntary and countries bargain over contributions to and the allocation of a central budget. We establish and explore the link between the budget's allocation and nations' contributions that occurs since bargaining power is endogenous, and a country's outside option during budget negotiations is to withdraw its contribution and consume its full income. Generically, it follows that unstructured bargaining gives an inefficient result in the presence of income asymmetry between member nations. Interestingly, redistribution arises endogenously, despite nations being purely self-interested. However, there exists a trade-off between increasing equality and decreasing efficiency, which becomes more severe as the centralized budget increases. We also analyze partial ex-ante commitment through alternative decision-making institutions: Both majority rule and exogenous tax rules can improve efficiency.
Keywords: H77; H87; D71; 330; Supranational Unions; Efficiency; Public Goods; Redistribution; Federalism; Legislative Bargaining; Wirtschaftsintegration; Öffentliche Güter; Allokationseffizienz; EU-Finanzbeziehungen; Politische Entscheidung; Souveränität; EU-Staaten